Like Vanessa - Charles, Tami (Charlesbridge, 2019)
It is 1983 and Vanessa Martin, a thirteen-year-old African American girl in Newark's public housing, dreams of following in the footsteps of the first black Miss America, Vanessa Williams; but the odds are against her until a new teacher at school organizes a beauty pageant and encourages Vanessa to enter.